(untitled) (Fiep Bulletin - online, 2014)
The concern with the quality of life comes gaining visibility with the media and with the increase of physical activity programs it brings the idea of Quality of Life. The gift had as objective to evaluate the auto-perception of the profile of the life style individually (Nahas, 2006), and the quality of life (WHOQOL _ Brief) of 14 athletes with visual deficiency, of an institution of governmental of Education for Deficient Appearances of the Ministry of Education with average age 26,94±7,07. The athletes had been selected in intentional way, had been used as instrument the questionnaires WHO-BREF(2005) composition for 26 questions, being two general questions of quality of partner-cultural and ambient the 24 life and excessively the 24 represent each one of facets that it composes the original instrument and also considered a set of individual parameters, that characterize the conditions where the person with visual deficiency lived. The general average of the 6 domains was used as classificatory parameter, understanding this average as value of classification, being this equal greater or the 14 (Q.V = Enough) and minor of whom 14 (Q.V = Insufficient). E the STYLE OF NAHAS LIFE (2006), thus forming the Pentacle of wellness formed from the answers to the closed questions that involve five components: nutrition, physical activity, preventive and historical behavior familiar e, relationships have controlled of stress.